KEBANGKITAN FEMINISME LIBERALISME (STUDI KASUS KONSEP DIRI PEMANDU LAGU KARAOKE) - Mukhroman, Iman; Gumelar, Rangga; Ahmad, Ikhsan (Program Studi Ilmu Komunikasi FISIP Universitas Sultan Ageng Tirtayasa, 2023)
English translation. This study was conducted to illustrate how the self-concept of karaoke song guides in the perspective of feminism liberalism in the veil of patriarchal ideology. Many values from the patriarchal ideological way of thinking later became an important part and had value in social life in Indonesian society. This ideology seems to easily give a negative label to women who have an activity or job related to service in a dark private space. The phenomenon of women who work as song guides today cannot be denied its existence. Women seem to be relegated to the values and norms that currently apply. Women song guides as a community have a self-concept with the value of freedom in it. The demands of work and often collide with moral and ethical values are often a discourse that is often a problem for them. The clash of cultures in the building of an ideological concept that they believe to be true as part of the thought of feminism liberalism, is not necessarily acceptable to all parties. With qualitative approaches and methods, this study tries to describe what then happens on the phenomenon of karaoke song guides that we often sneer and aginalize. In-depth observation and interviews are recognized techniques as validation in qualitative research, including triangulation by researchers.